2016
DOI: 10.1016/j.phrs.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

SRPK1 inhibition in prostate cancer: A novel anti-angiogenic treatment through modulation of VEGF alternative splicing

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
2
25
0
2
Order By: Relevance
“…To date, SRPK1 has been shown to be overexpressed in different types of cancers, and several mechanisms were reported to be responsible for its oncogenic role. SRPK1 could regulate VEGF splicing through phosphorylation of the splice factor SRSF1 and thus promote tumor angiogenesis of prostate cancers (Bullock et al, 2016;Mavrou & Oltean, 2016;Morooka et al, 2015), some studies also showed that SRPK1 can promote Akt phosphorylation to affect cell proliferation of hepatocellular carcinomas and contribute to GC whole-transcript expression analysis for SRPK1 knockdown cells, we found a majority of snoRNAs were decreased with SRPK1 silencing.…”
Section: Discussionsupporting
confidence: 50%
“…To date, SRPK1 has been shown to be overexpressed in different types of cancers, and several mechanisms were reported to be responsible for its oncogenic role. SRPK1 could regulate VEGF splicing through phosphorylation of the splice factor SRSF1 and thus promote tumor angiogenesis of prostate cancers (Bullock et al, 2016;Mavrou & Oltean, 2016;Morooka et al, 2015), some studies also showed that SRPK1 can promote Akt phosphorylation to affect cell proliferation of hepatocellular carcinomas and contribute to GC whole-transcript expression analysis for SRPK1 knockdown cells, we found a majority of snoRNAs were decreased with SRPK1 silencing.…”
Section: Discussionsupporting
confidence: 50%
“…SRPK1 expression increases in prostate cancer (Bullock and Oltean 2016 ; Bullock et al 2016 ; Mavrou et al 2015 ). Existing drugs are available that can target SRPK1 and have already been tested in mouse models (Mavrou et al 2015 ; Mavrou and Oltean 2016 ). A further important kinase that might impact on prostate cancer pathology is aurora A, which affects the production of ARv splice variants, likely also through control of SRSF1 (Jones et al 2017 ).…”
Section: Splicing Regulators Can Change Expression Patterns In Prostamentioning
confidence: 99%
“…Analogically, ERK may also regulate the phosphorylation and functions of SRPK1, but this will need more evidence to verify. Besides ERK and AKT, SRPK1 can activate several other tumor-related proteins in distinct tumor types, such as JNK [ 27 ] and VEGFs [ 28 30 ]. Certain up-stream regulators for SRPK1 were also identified, including RhoA [ 31 ], Wnt [ 15 ], TGF-β [ 27 ], long non-coding RNAs [ 25 ] and human papillomavirus type 1 E1^E4 protein [ 32 ].…”
Section: Discussionmentioning
confidence: 99%